Proceedings of the Proceedings of the 1st International Conference on Language and Language Teaching, ICLLT 2019, 12 October, M 2020
DOI: 10.4108/eai.12-10-2019.2292229
|View full text |Cite
|
Sign up to set email alerts
|

Preparing English Department Students for Industry 4.0 Era through Critical Thinking Skills Development

Abstract: The purpose of this review is to shed light on how to build critical thinking skills as one of the necessary skills that all students in higher education level need to be able to compete in the Industry 4.0 era. To ensure success, the worldwide industries in the fourth industrial revolution require their workforce to have not only technical skills but also soft skills, particularly critical thinking skills. With this new trend, English Department students are challenged to develop their critical thinking skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…In terms of the teaching and learning process, responses given by 157 participants (72.7%) showed that the lecturers' performance in teaching did affect the results of their learning process. This finding is in a similar vein with those of previous studies (Abidin et al, 2012;Adachi, 2015;Al-Sobhi et al, 2018;Anggraeni, 2018;Burgos & Pérez, 2015;Mbato & Kharismawan, 2018;Nduwimana, 2019;Sulistiyo & Haswindy, 2018;Yosintha & Arochman, 2020). Burgos and Pérez (2015) claim that students tend to prefer lecturers who use both their first language and English when teaching and thus providing them with richer exposures to authentic English.…”
Section: Who Investigatedsupporting
confidence: 89%
See 2 more Smart Citations
“…In terms of the teaching and learning process, responses given by 157 participants (72.7%) showed that the lecturers' performance in teaching did affect the results of their learning process. This finding is in a similar vein with those of previous studies (Abidin et al, 2012;Adachi, 2015;Al-Sobhi et al, 2018;Anggraeni, 2018;Burgos & Pérez, 2015;Mbato & Kharismawan, 2018;Nduwimana, 2019;Sulistiyo & Haswindy, 2018;Yosintha & Arochman, 2020). Burgos and Pérez (2015) claim that students tend to prefer lecturers who use both their first language and English when teaching and thus providing them with richer exposures to authentic English.…”
Section: Who Investigatedsupporting
confidence: 89%
“…In addition, to ensure success in Industry 5.0, this study found that effective cooperation between education institutions and the world of industry is fundamental as suggested in a plethora of studies in various fields Mbato & Kharismawan, 2018;Silalahi, 2017;Wichmann et al, 2019;Yosintha & Arochman, 2020). Students should be equipped with the competencies instrumental in Industry 5.0, not only competencies specific to their field but also those required for successful employment in general.…”
Section: General Attitude Towards Industry 50mentioning
confidence: 95%
See 1 more Smart Citation
“…As the maritime industry increasingly focuses on sustainability, integrating environmental education into Maritime English aligns with industry trends and future workforce needs. This alignment can make graduates more attractive to employers and contribute to the industry's efforts to reduce its environmental impact [9,13].…”
Section: Alignment With Industry Trendsmentioning
confidence: 99%
“…According to Ardiyani et al, (2020) critical thinking is also one of the abilities that should be possessed by graduates who are ready to work. This ability is defined as the ability to think clearly and rationally concerning a problem or situation and then find the best solution (Yosintha & Arochman, 2020).…”
Section: Introductionmentioning
confidence: 99%